Millie Shares - Alexander, Claire (London Egmont Press, 2014)
Millie loves her monkey. He is her very special toy. But when best friend Lily wants to play with Monkey too, Millie is not happy. She takes away all the toys and plays with them by herself. Will Millie ever learn to share? This picture book is perfect for any child who finds sharing impossible.